Healthcare resource use and relapses with fingolimod versus natalizumab for treating multiple sclerosis: a retrospective US claims database analysis. (August 2014) - Bergvall, Niklas; Lahoz, Raquel; Reynolds, Tracy; Korn, Jonathan R.
Abstract Objective: Healthcare resource utilization in patients with multiple sclerosis (MS) is linked to relapses and disease progression. This retrospective cohort database analysis compared healthcare resource use and proxy measures of relapse outcomes in patients with active disease who switched to fingolimod or natalizumab. Methods: Using administrative claims data from the US PharMetrics Plus database, we identified patients with an MS diagnosis and a claim for fingolimod or natalizumab between 1 October 2010 and 30 June 2012 (index period) who had experienced a relapse (identified using a claims-based algorithm) and used other disease-modifying therapies (DMTs) in the previous year. Patients in the fingolimod and natalizumab cohorts were propensity score matched (1:1). MS-related inpatient stays, corticosteroid use and the proportion of patients experiencing claims-based relapses were assessed in the pre-index and post-index persistence periods. Time to first claims-based relapse in the post-index persistence period was assessed using a Kaplan–Meier curve. Results: The study included 623 unmatched patients (299 and 324 patients in the fingolimod and natalizumab cohorts, respectively) and 370 matched patients (185 in each cohort). In the matched analysis, MS-related inpatient stays and corticosteroid use were similar in the fingolimod and natalizumab cohorts during the post-index persistence period, and were significantly reduced versus the pre-index period (p < 0.01). A similar proportion of patients in the fingolimod and natalizumab cohorts were free from claims-based relapses in the persistence period (68.1% and 68.6%, respectively). There was no significant difference in the likelihood of experiencing a claims-based relapse (p = 0.8696). Limitation: Identification of relapses is based on database claims rather than on clinical assessment. Conclusions: In analyses of patients with MS with a history of relapse and DMT use, fingolimod and natalizumab reduce healthcare resource utilization and have similar effectiveness in a real-world setting.